(untitled) - Leibson, Steve (Amsterdam,Boston, 2006)
Designing SOCs with Configured Processor Cores is an essential reference for system-on-chip designers. This well-written book gives a practical introduction to three basic techniques of modern SOC design: use of optimized standard CPU and DSP processors cores, application-specific configuration of processor cores, and system-level design of SOCs using configured cores as the key building block. Readers will find it is often the first book they reach for in defining and designing their next chip.
Keywords: Embedded computer systems,Systems on a chip,Hệ thống máy tính được cài đặt; Design and construction,Design and construction,Cấu trúc và thiết kế